Chromosome fragility in the buccal epithelium in patients with Fanconi anemia. (1st March 2020) - Ramírez, María José; Minguillón, Jordi; Loveless, Sara; Lake, Kelly; Carrasco, Estela; Stjepanovic, Neda; Balmaña, Judith; Català, Albert; Mehta, Parinda A.; Surrallés, Jordi
Abstract: Fanconi anemia (FA) is a rare genome instability syndrome characterized by progressive bone marrow failure and predisposition to cancer, especially head and neck squamous cell carcinoma. Surgical resection is the standard of care for solid tumors, as patients with FA do not tolerate genotoxic chemotherapies or radiation, leading to poor prognosis. It is therefore imperative to develop chemoprevention strategies such as the identification of novel biomarkers to detect the formation of the tumor before its emergence and to use them in clinical trials aimed to counteract genome instability of patients with FA in tissues at risk. Micronuclei (MN) are chromosome fragments that are left behind in anaphase and appear in daughter cells as small additional nuclei. In this work, we analyzed MN frequencies in exfoliated buccal cells from 40 patients with FA and 24 controls. We found that MN frequency was significantly increased in the FA cohort indicating that we can detect chromosome fragility in patients with FA in basal conditions and in a tissue that is divided in vivo . Consequently, the MN assay in exfoliated buccal cells of patients with FA could be used in cancer risk studies and clinical trials aimed to identify cancer chemopreventive drugs. Highlights: First evidence that patients with FA have significantly elevated frequencies of micronuclei in buccal cells. Micronuclei in buccal cells of patients with FA are a novel in vivo biomarker of DNA damage useful in chemoprevention studies. Track the frequency of micronuclei in buccal cells in patients with FA can help to detect changes prior to SCC onset.